Phương pháp san số mũ trong dự đoán dãy chỉ tiêu kinh tế - Dat, Tran Tho; Huy, Vu Quoc (Journal of Computer Science and Cybernetics, 2018)
This article concentrates on the content of the method of exponential smoothing in forecasting economic series, the use of signal of D.W.Trigg and A.G.Leach. However, in many case, such a direct use can make big errors. The author asks to use the signal to control the forecasting model and the correction of adaptive parameter is made by the conversation between men and computers.